Rapid rooting medium for Chinese tamarisk and Chinese tamarisk tissue culture method - MA JUNMEI; WANG JING; LIU YOUJUN; CHAI CHENGWU; WANG FANGLIN; ZHANG JINCHUN (2017)
The invention discloses a rapid rooting medium for Chinese tamarisk and a Chinese tamarisk tissue culture method. The medium takes the 1/2MS medium as the basic medium, indolebutyric acid and cane sugar are added, and the pH value of the medium is 5.8-6.0. an explant of Chinese tamarisk is subjected to cleaning, disinfection and induced culture to generate cluster buds, the cluster buds are placed in the above medium for culture, rooting speed of the Chinese tamarisk tissue culture plants is increased, about 40 days are required for the whole rooting process, the rooting time is neat, the rooting amount is large, the seedling is strong after rooting, the leaves are tender green, the growth is good; in addition, the method has the characteristics of fast breeding speed, high seedling rate, and short culture period, and can provide favorable condition for large-scale factory production. The roots of the Chinese tamarisk are developed, the Chinese tamarisk has good wind erosion resistant, sand burying resistant